Method for detection and identification of multiple chromosomal integration sites in transgenic animals created with lentivirus. (December 2006) - Bryda, Elizabeth C.; Pearson, Michael; Agca, Yuksel; Bauer, Beth A.
Transgene delivery systems, particularly those involving retroviruses, often result in the integration of multiple copies of the transgene throughout the host genome. Since site-specific silencing of trangenes can occur, it becomes important to identify the number and chromosomal location of the multiple copies of the transgenes in order to correlate inheritance of the transgene at a particular chromosomal site with a specific and robust phenotype. Using a technique that combines restriction endonuclease digest and several rounds of PCR amplification followed by nucleotide sequencing, it is possible to identify multiple chromosomal integration sites in transgenic founder animals. By designing genotyping assays to detect each individual integration site in the offspring of these founders, the inheritance of transgenes integrated at specific chromosomal locations can be followed efficiently as the transgenes randomly segregate in subsequent generations. Phenotypic characteristics can then be correlated with inheritance of a transgene integrated at a particular chromosomal location to allow rational selection of breeding animals in order to establish the transgenic line.